O garantismo como vetor humanista ao processo penal - Bento, Patricia Stucchi (2013)
This doctorate thesis has the objective to show the criminal garantism theory and its wide range of application, such as national and international law. The search presents the theory harmony with effective constitutional principles in Democratic State countries. This study approach the garantism and its compatibility with state punitive intention; contradict the wrong idea of being one excessive protection of the criminal law offender supporting that, in reality, derives from the human dignity principle which final receiver is the human being. The humanist vector of criminal procedure is the view given to the garantism, competing to him impose state limits to reach punitive intention, without dispensing necessary preservation constitutional rights, guarantees and liberties and the human dignity principle observance. The garantism defense was chosen some aspects, which will be object of more concentration. Between then, the fact of the citizen have the freedom right The search recovers the first humanists ideas with law relation of the legal basis appearance and the theory dissemination that, actuality is recognized by many countries legislation. In Brazil, were chosen some criminal procedure stages that its applicability can be verified. At the end, are presented foreigner legislation models with garantism basis that, in many aspects, are similar to Brazilian legislation, especially as for the intention of refining continually the treatment given to the offender with humanist legislation basis